Long-Term Protection Elicited by a DNA Vaccine Candidate Expressing the prM-E Antigen of Dengue Virus Serotype 3 in Mice - Feng, Kaihao; Zheng, Xiaoyan; Wang, Ran; Gao, Na; Fan, Dongying; Sheng, Ziyang; Zhou, Hongning; Chen, Hui; An, Jing (Frontiers in Cellular and Infection Microbiology, 2020)
Dengue virus (DENV) is the causative agent of dengue, and its incidence has increased thirty-fold in the past five decades. Among the four cocirculating serotypes, DENV3 is associated with an increased number of severe infections and has become widespread. Vaccination is the mainstay of prevention in reducing disease burden. Previously, the protective efficacy of DNA vaccine candidates towards DENV1, 2, and 4 was confirmed in mice. In this study, a DNA vaccine candidate (pVAX1-D3ME) expressing the prM and E proteins of DENV3 was constructed, and then the immunogenicity and protection were assessed in mice to further develop a tetravalent dengue vaccine. Moreover, the cross-reactive immune responses against the other three serotypes were investigated. The results showed that three doses of 50 μg of pVAX1-D3ME were sufficient to induce strong antigen-specific T cell responses and robust and consistent neutralizing antibodies. Additionally, immunization with pVAX1-D3ME offered protective immunity against not only DENV3 but also the other three serotypes, which could be observed even after 12 months. This study shows great promise for the further evaluation of a dengue tetravalent DNA vaccine candidate in large animal models, including nonhuman primates.